2023
DOI: 10.3390/biomedicines11072002
|View full text |Cite
|
Sign up to set email alerts
|

H3G34-Mutant Gliomas—A Review of Molecular Pathogenesis and Therapeutic Options

Abstract: The 2021 World Health Organization Classification of Tumors of the Central Nervous System reflected advances in understanding of the roles of oncohistones in gliomagenesis with the introduction of the H3.3-G34R/V mutant glioma to the already recognized H3-K27M altered glioma, which represent the diagnoses of pediatric-type diffuse hemispheric glioma and diffuse midline glioma, respectively. Despite advances in research regarding these disease entities, the prognosis remains poor. While many studies and clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 143 publications
0
5
0
Order By: Relevance
“…Embryonal tumor morphology is a pattern of some H3G34-altered DHGs. They also tend to be tumors seen in older children or early adulthood, which is not a characteristic of our group 23 . According to Yeo et al, 24 there could be 9% IDH mutant adult-type gliomas in our study, but that does not affect the importance of the MMR status of the tumors.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Embryonal tumor morphology is a pattern of some H3G34-altered DHGs. They also tend to be tumors seen in older children or early adulthood, which is not a characteristic of our group 23 . According to Yeo et al, 24 there could be 9% IDH mutant adult-type gliomas in our study, but that does not affect the importance of the MMR status of the tumors.…”
Section: Discussionmentioning
confidence: 46%
“…They also tend to be tumors seen in older children or early adulthood, which is not a characteristic of our group. 23 According to Yeo et al, 24 there could be 9% IDH mutant adult-type gliomas in our study, but that does not affect the importance of the MMR status of the tumors. Suwala et al 25 have suggested that primary dMMR IDH mutant astrocytoma have the worst clinical outcome.…”
Section: Discussionmentioning
confidence: 48%
“…This study revealed that ONC201 disrupts integrated metabolic and epigenetic pathways, leading to a reversal of pathognomonic H3K27me3 reduction [ 93 , 102 ]. In the G34R/V mutation, it has been shown that it does not directly participate in the methylation of G34, but affects the methylation of the adjacent K36 (H3 K36me2/3) [ 150 ]; however, unlike K27M, the manner in which G34R/V exerts its dominant effect on H3 biology and results in tumorigenesis remains to be elucidated [ 151 ].…”
Section: Clinical Practice and Molecular Markermentioning
confidence: 99%
“…The epidemiology of diffuse hemispheric glioma with H3 G34 mutation shows a slight male predominance and a typically more aggressive course than other pediatric brain tumors [ 119 ]. This mutation is less common than the H3 K27M mutation found in midline gliomas, with specific genetic and clinical features that differentiate them from other glioma subtypes [ 121 ].…”
Section: Diffuse Hemispheric Glioma H3 G34-mutantmentioning
confidence: 99%
“…Driving mutation here is a missense mutation of the H3F3A gene, eventually causing glycine 34 to be replaced by arginine or valine in the mature protein [ 121 ]. While G34 is not subject to methylation, this particular mutation leads to changes that inhibit binding of regulatory proteins and ultimately causes transcriptional reprograming [ 3 , 105 ].…”
Section: Diffuse Hemispheric Glioma H3 G34-mutantmentioning
confidence: 99%